Fibrosis and Sports Injuries: Concept and Implications: The Gesmute-Setrade Consensus Statement - Cofre-Bolados, C (SAGE Publications Ltd, 2024)
Background: Musculoskeletal fibrosis can be frequently observed in the scope of sports medicine; however, there is no consensus regarding its definition, nor do we have substantial knowledge regarding its epidemiology or best therapeutic alternatives. Purpose: The GESMUTE (Group for the Study of the Muscle Tendon System) Epidemiology Group, integrated into SETRADE (The Spanish Society for Sports Traumatology) propose a definition for musculoskeletal fibrosis within the field of physical exercise. Study Design: Consensus statement. Methods: A bibliographic review of the existing scientific evidence and consensus was developed by the authors on the definition of fibrosis in the field of sport. Results: Our working group proposed the definition of fibrosis as an abnormal accumulation of extracellular matrix, usually with regards to an injury complication, showing various clinical findings affecting muscles, tendons, ligaments, articular capsules and nerves which, in turn, mars the recovery process, causing symptoms and finally leading to relapses. Conclusion: Fibrosis in sport may be considered as an abnormal accumulation of extracellular matrix, usually related to complications of an injury, showing a wide range of clinical symptomatology, affecting muscles, tendons, ligaments, articular capsules, and nerves. © The Author(s) 2024.